2020
DOI: 10.1371/journal.pone.0236919
|View full text |Cite
|
Sign up to set email alerts
|

Mountaineers on Mount Everest: Effects of age, sex, experience, and crowding on rates of success and death

Abstract: Mount Everest is an extreme environment for humans. Nevertheless, hundreds of mountaineers attempt to summit Everest each year. In a previous study we analyzed interview data for all climbers (2,211) making their first attempt on Everest during 1990-2005. Probabilities of summiting were similar for men and women, declined progressively for climbers about 40 and older, but were elevated for climbers with experience climbing in Nepal. Probabilities of dying were also similar for men and women, increased for clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…BP’s positive correlation with Temp and negative correlation with Wind recorded for non-winter ascents of Everest and K2 supported the proposal by Moore and Semple (2011 , 2012) for Everest climbers that summit BP can act as a simple and easily implementable predictor of the risk of hypothermia and frostbite. Huey et al (2020) suggested that improved weather forecasting was one reason for the increased likelihood of summiting Everest and the lower likelihood of mountaineers dying over the past 15 years compared with 1990–2005. Therefore monitoring of Temp and BP in the base camp and at higher camps, as during the first Everest expeditions almost 100 years ago ( Moore et al, 2010 ), should become standard practice to correct more general forecasts for high-altitude expeditions.…”
Section: Discussionmentioning
confidence: 99%
“…BP’s positive correlation with Temp and negative correlation with Wind recorded for non-winter ascents of Everest and K2 supported the proposal by Moore and Semple (2011 , 2012) for Everest climbers that summit BP can act as a simple and easily implementable predictor of the risk of hypothermia and frostbite. Huey et al (2020) suggested that improved weather forecasting was one reason for the increased likelihood of summiting Everest and the lower likelihood of mountaineers dying over the past 15 years compared with 1990–2005. Therefore monitoring of Temp and BP in the base camp and at higher camps, as during the first Everest expeditions almost 100 years ago ( Moore et al, 2010 ), should become standard practice to correct more general forecasts for high-altitude expeditions.…”
Section: Discussionmentioning
confidence: 99%
“…Everest's upper slopes ( Matthews et al, 2020 ). Added impetus for this development may be provided if future research determines that oxygen availability has a detectable influence on mountaineering success and safety, perhaps including for those climbing with supplemental oxygen ( Fontanarosa et al., 2000 ; Huey et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 One example for an expedition setting in which this issue relevant is Mount Everest, where approximately 1000 people ascend each year, with 54% of Everest climbers from 2006 to 2019 being ≥40 y old and 85% being male. 11 Considering these demographics, there is a reasonable likelihood that a few climbers per year experience acute urinary retention related to BPH as they attempt to summit the peak.…”
Section: Urinary Retentionmentioning
confidence: 99%